2013
DOI: 10.1002/chem.201300168
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Inverse‐Electron‐Demand Hetero‐Diels–Alder Reactions Catalyzed by Modularly Designed Organocatalysts

Abstract: MDO rocks! Proline and (2S,3aS,7aS)‐octahydro‐1H‐indole‐2‐carboxylic acid are both poor catalysts for the inverse‐electron‐demand hetero‐Diels–Alder reactions between aldehydes and electron‐deficient enones. However, forming modularly designed organocatalysts (MDOs) through their self‐assembly with cinchona alkaloid‐derived thioureas can dramatically improve the efficiency of these catalysts (see scheme; PCC=pyridinium chlorochromate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…A few years back we introduced modularly designed organocatalysts (MDOs), which could self‐assemble under the reaction conditions from carefully designed precatalyst modules through ionic interactions, for catalyzing organic reactions . Recently, we successfully applied MDOs in organocatalyzed domino reactions.…”
Section: Synergistic Organocatalysismentioning
confidence: 99%
“…A few years back we introduced modularly designed organocatalysts (MDOs), which could self‐assemble under the reaction conditions from carefully designed precatalyst modules through ionic interactions, for catalyzing organic reactions . Recently, we successfully applied MDOs in organocatalyzed domino reactions.…”
Section: Synergistic Organocatalysismentioning
confidence: 99%
“…At the same time, Zhao and co‐workers reported self‐assembled catalysts based on proline derivatives and cinchona‐alkaloid‐derived thioureas to be highly efficient catalysts for inverse‐electron‐demand hetero‐Diels–Alder cycloaddition of electron‐deficient enones and aldehydes (Scheme ) . When l ‐proline ( 7a ) and quinidine–thiourea 8a were used as the catalyst in toluene at room temperature the reactions between enones 77 and propanal generated mixtures of the aldol products and the hetero‐Diels–Alder products 79 in ratios of about 1:4 after 3 h. Prolonging the reaction time to 5 h led to almost exclusive formation of the hetero‐Diels–Alder products 79 in 92 % yield, as mixtures of two anomers (ratio 80:20), which were oxidized with pyridinium chlorochromate (PCC) to give the dihydropyranone derivatives 80 as single trans diastereomers in 90 % ee .…”
Section: Cycloadditionsmentioning
confidence: 99%
“…Zhao et al demonstrated that MDO self-assembled from proline derivatives and cinchona alkaloid derived thioureas are highly efficient catalysts for inverse-electron-demand HDA reactions [103]. They developed highly enantioselective HDA reactions of electron-deficient enones 111 and aldehydes 112 by using MDO (Scheme 20).…”
Section: Inverse-electron-demand Hetero-diels–alder Reactions Of 1-oxmentioning
confidence: 99%
“…β,γ-Unsaturated α-ketophosphonates 111 may also be applied in these reactions if a higher loading of the precatalyst modules (10 mol%) is used. The authors proposed a plausible transition state on the basis of the product 116 stereochemistry and the MDO structure [103]. They showed that the aldehyde 112 reacts with the OHIC moiety of the MDO to form an ( E) -enamine.…”
Section: Inverse-electron-demand Hetero-diels–alder Reactions Of 1-oxmentioning
confidence: 99%